Can eight weeks of stabilization exercise change the amount of peak vertical ground reaction forces during single leg drop landing? - Fatahi, F.; Ghasemi, G.; Karimi, M. (Sport Science - International Scientific Journal of Kinesiology, 2017)
The purpose of this study was to investigate the kinetics during single leg drop landing test following a CST intervention. The present research was a quasi-experimental study with pretest/posttest and a control group. After giving their informed written consent, 30 athletes (15 in the experimental group, and 15 in the control group) volunteered to participate in the training program consisting of CST sessions, 3 times per week for 8 weeks. The training group performed the CST during 8 weeks, but the control group did not perform these exercises. Kinetic variables in pretest and posttest during single-leg drop landing were measured by motion analysis and a force plate device. Data were analysed using mixed ANOVA repeated measure significance level of P < 0.05. The results revealed that the peak vertical ground reaction forces, loading rate, and average loading rate signi.cantly reduced following an 8 weeks CST intervention (P<0.05). This study shows evidence that core stability training improves landing kinetics, and may reduce lower extremity injury risk in athletes.